2014
DOI: 10.1111/jsbm.12141
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Criteria for Grounding Entrepreneurship Education and Training Programs: A Validation Study

Abstract: The entrepreneurship literature lacks a systematically developed and validated framework to ground educational programs. We previously developed behavioral observation scales (BOS) consisting of 9 dimensions and 47 behaviors. In this study, we validated the BOS using 12 performance measures and a national survey of 149 entrepreneurs. The BOS were found to be valid. All 9 BOS dimensions, as well as the total score on the BOS, correlated significantly with many of the 12 nonbehavioral performance measures. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 114 publications
(166 reference statements)
0
23
0
Order By: Relevance
“…We took several steps to minimize bias (such as leniency) in this study, particularly as it concerns self‐BOS ratings. First, the BOS assessed performance using a 5‐point frequency measure as frequency measures minimize bias compared to more evaluative (e.g., “poor,” “good,” “excellent”) performance measures (see review in Brown & Hanlon, ). Second, we informed participants that feedback from others—in this case, workplace observers—would be used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took several steps to minimize bias (such as leniency) in this study, particularly as it concerns self‐BOS ratings. First, the BOS assessed performance using a 5‐point frequency measure as frequency measures minimize bias compared to more evaluative (e.g., “poor,” “good,” “excellent”) performance measures (see review in Brown & Hanlon, ). Second, we informed participants that feedback from others—in this case, workplace observers—would be used.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we used participant's scores on behavioral observation scales (BOSs; Latham & Wexley, ). Several studies have shown that BOSs correlate with other, nonbehavioral, performance measures including Grade Point Average (GPA) (Brown & Latham, ) and entrepreneurial performance (Brown & Hanlon, ). Thus, BOSs represent a valid and reliable performance appraisal where the frequency with which a set of performance‐relevant behaviors is performed is assessed on a 5‐point Likert‐type scale (Latham & Wexley, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entrepreneurship action and practice race far ahead of entrepreneurship research and teaching (Rideout and Gray, 2013). Brown and Hanlon (2016) explained that the probably main reasons for this are that entrepreneurship studies are more literature‐based than practice‐based, and that entrepreneurship theory is diverse but fragmented. These two reasons lead to entrepreneurship education lacking empirical rigor.…”
Section: Surveying Entrepreneurship Study: Various Academic Topicsmentioning
confidence: 99%
“…Furthermore, entrepreneurship education is hardly standardized, because all participants in the entrepreneurship education − regardless of whether they are students, teachers, or other stakeholders − form a complex and diverse relationship. Each participant has his or her own backgrounds, values, and personality, and has different expectations and aspirations (Brown and Hanlon, 2016). Recent research found that most successful entrepreneurs are people in their late 30s or early 40s, rather than young people or students (Azoulay et al ., 2018) Correspondingly, Johannisson (2016) provided three suggestions for future entrepreneurship education: entrepreneurship education should include more external partnership, entrepreneurship education should teach students how to develop social skills and build social networks, and teachers in entrepreneurship education have to have both conceptual knowledge and practice knowledge.…”
Section: Surveying Entrepreneurship Study: Various Academic Topicsmentioning
confidence: 99%
“…With saturated job market, and the huge youth population governments all across the world along with higher education commissions have aimed at proliferation of entrepreneurship development programs, incubation centers, startup competitions. The purpose is to increase the supply of entrepreneurs and improve their chances of success (Brown & Hanlon, 2016). GEM data base captures 12 of these entrepreneurship support conditions as entrepreneurial framework conditions (EFCs) on national level.…”
Section: Introductionmentioning
confidence: 99%